Características Psicométricas do Young Positive Schema Questionnaire (YPSQ) – versão brasileira - Soares, Emyli de Sousa (2023)
Early Adaptive Schemes (EIAs) are developed when the cultural and family context adequately responds to people's basic emotional needs. These are adapted broad and pervasive themes or patterns associated with memories, emotions, cognitions and neurobiological reactions. They are developed in childhood and adolescence, elaborated throughout life, and lead to healthy functioning and behaviors. The objectives of this study were to carry out a systematic review of the literature on the Young Positive Schema Questionnaire (YPSQ); perform a cross-cultural adaptation and obtain content validity evidences from the YPSQ; to obtain construct validity evidences of the YPSQ (exploratory factorial structure of the YPSQ - Brazilian version) and to investigate its divergent validity in relation to the YSQ-s3. In the systematic review, 5 studies were found that investigated validity evidences of the YPSQ, three of them in English, one in Chinese and another in German; in the procedure for obtaining content validity evidences, the instrument was translated into Portuguese by bilingual psychologists and also underwent a back-translation process; 2 samples of expert judges participated, one with 10 and another with 6 participants and a target population sample with 11 individuals. From the answers, the Content Validity Coefficient was calculated according to the judges' answers for the criteria of Clarity, Practical Pertinence and Theoretical Relevance, and of the target population only for the criterion of Clarity. Some items did not reach a satisfactory level in the Clarity criterion in the target population. The Practical Pertinence and Theoretical Relevance criteria all reached a satisfactory level. The results indicated that, considering the semantic bias, the instrument measures what it suggests to measure, thus having evidence of content validity for the Brazilian context (CVC: from 0.56 to 1.00). A total of 365 individuals between 18 and 65 years old participated in the investigation of construct validity evidence. After exploratory factor analysis, 7 factors were found in the Brazilian version of the YPSQ: 1) discipline/competence/success; 2) social belonging; 3) self-compassion/health and safety; 4) secure attachment/trust; 5) emotional openness/spontaneity; 6) healthy self-interest/self-care/self-direction; 7) empathic consideration/respect for others. All alphas found were above 0.7, the lowest alpha being 0.71 (empathic consideration/respect for others) and the highest 0.89 (social belonging). The divergent validity study indicated that all correlations were significant and negative, except for the correlation between the discipline/competence/success factor of the Brazilian translation of the YPSQ and the “inflexible standards” factor of the YSQ-s3. The YPSQ – Brazilian version has 44 items, 12 less than its original English version, which has 56 items. This work enabled the cultural adaptation and obtaining evidence of content and construct validity for the Brazilian population. As the validity indexes obtained were satisfactory, the use of the YPSQ – Brazilian version in clinical interventions in schema therapy is proposed.